POLA PERMUKIMAN PRASEJARAH: KAJIAN ATAS DATA HASIL PENELITIAN MEGALITIK DI PAKAUMAN, BONDOWOSO - Diman Suryanto (BRIN, 2002)
This settlement study is based on the results of research at the Pakauman site, Pakauman Village, Grujugan District, Bondowoso Regency, East Java Province, in 1985. This study is very important because at the Pakauman site which contains many megalithic remains, a wood processing factory has now been established.